Cold drawing preparation method for bright surface of high-strength titanium alloy wire

By forming an inorganic salt lubricating film on the surface of the titanium alloy wire and cold drawing is performed using a pressurized mold, the problem of oxide scale in the hot drawing of titanium alloy wire is solved, the tensile strength and material yield of the wire are improved, and efficient preparation of cold drawing on bright surfaces is achieved.

CN119702728AActive Publication Date: 2025-03-28INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411889400.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

In the thermal drawing process of existing titanium alloy wire materials, the peeling is required after the scale is produced, resulting in low material yield and increased oxygen content, and the pulling speed is slow, and the metallographic phase is uncontrollable.

Method used

The lubrication treatment of the pressurized mold and the surface lubrication treatment of titanium alloy wire is combined. Cold drawing is performed under the bright surface state of titanium alloy to form an inorganic salt lubricating film. The lubricating film is brought into the compression area of ​​the mold through the pressurized mold drawing, achieving sliding friction and achieving the effect of bright surface drawing.

Benefits of technology

The tensile strength of the wire material is improved, and the problems of low material yield, increased oxygen content, slow drawing speed and uncontrollable metallographic phase are solved, so as to achieve the preparation of cold drawing of high-strength titanium alloy wire material on the bright surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119702728A_ABST
    Figure CN119702728A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of metallurgy, and relates to a preparation method of a titanium alloy wire, in particular to a bright surface cold drawing preparation method of a high-strength titanium alloy wire. According to the method, the titanium alloy wire is subjected to vacuum heat treatment and surface lubricating treatment, then a multi-group multi-pass bright surface cold drawing process is performed, and finally the titanium alloy wire with the target diameter is obtained through surface treatment. By controlling the pass deformation to be 8%-20% and the heating number deformation to be 30%-50%, whole-course bright surface cold drawing of the titanium alloy wire with the diameter being 3.0 mm-0. 2 mm is achieved, and the drawing speed reaches 15-35 m / min. The prepared titanium alloy wire is good in metallographic structure and high in uniformity, and the yield reaches up to 80% or above. For the filaments with the diameter of 0.5 mm-0. 2 mm, due to bright surface drawing, the problem that the frequency of easy breakage of the filaments is increased due to the fact that pits are brought to the surfaces of the filaments due to treatment of oxide skin on the surfaces of the filaments is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metallurgy and relates to a method for preparing a titanium alloy wire, in particular to a method for preparing a high-strength titanium alloy wire with a bright surface by cold drawing. Background Art

[0002] Titanium alloy TC4ELI has excellent comprehensive mechanical properties, corrosion resistance and good biocompatibility. It has broad application scenarios in aviation, aerospace, shipbuilding, chemical industry, sports equipment and medical fields, and has achieved large-scale commercial use. TC4ELI is also the main raw material for medical cables due to its low impurity elements and high strength. Medical cables are mainly used in the medical field to fix and support the waist, help patients recover and protect body parts, and are suitable for the treatment and rehabilitation of various lumbar diseases. Therefore, medical cables are usually required to have high tensile strength. TC4ELI is obtained by a cold drawing process of heat treatment and solid solution to obtain high-strength wire, which is also the preferred wire material for medical cables.

[0003] The drawing process of titanium alloy wire includes cold drawing, hot drawing and warm drawing, among which cold drawing, i.e. drawing below the recrystallization temperature, is the most commonly used processing method. The most efficient cold drawing methods are roller die drawing and die drawing. Due to the limitation of the die structure, roller die drawing has difficulty in drawing fine wires below φ2.0mm; traditional die drawing requires oxide scale as a lubricating carrier, and oxygen increase is inevitable during processing. In the end, oxygen needs to be treated, which is complex and costly. Oxide scale will be produced during hot drawing, and the process of removing the oxide scale requires multiple peeling, resulting in low yield and increased oxygen content. At the same time, there are technical problems such as slow drawing speed and uncontrollable metallographic structure. Warm drawing is drawing at a temperature of 300-400℃. Its disadvantages are high wire resistance during drawing and low wire strength after drawing. Summary of the invention

[0004] The present invention provides a method for preparing a high-strength titanium alloy wire with a bright surface by cold drawing. The method combines a supercharged die and a titanium alloy wire surface lubrication treatment to draw the wire under the bright surface state, forming an inorganic salt lubricating film on the wire surface. While forming a film lubrication interface, the supercharged die is used to draw the lubricating film into the compression area of ​​the die, and sliding friction is achieved on the wire surface, thereby achieving the effect of bright surface drawing. The method is used to solve the technical problems of low yield and increased oxygen content caused by the need for multiple peeling after the oxide scale is generated during the hot drawing process of titanium alloy wire. At the same time, the grains are refined, the tensile strength of the wire is improved, and the problems of slow drawing speed and uncontrollable metallographic structure are solved.

[0005] The technical solution of the present invention is as follows:

[0006] A method for preparing a high-strength titanium alloy wire with a bright surface by cold drawing comprises the following steps:

[0007] (1) Taking titanium alloy wire raw material;

[0008] (2) subjecting the titanium alloy wire to vacuum heat treatment and surface lubrication treatment;

[0009] (3) performing multiple groups of multiple passes of bright surface cold drawing processes, and performing vacuum heat treatment and surface lubrication treatment between each group of cold drawing processes;

[0010] The multi-group multi-pass bright surface cold drawing process,

[0011] A. When the target diameter is 1.0-3.0mm, the number of groups is 3-6, the number of passes in each group is 2-6, the deformation of each pass is 8%-20%, and the deformation of each fire is 30%-50%;

[0012] Or B, when the target diameter is 0.2-1.0mm, the number of groups is 3-6, the number of passes in each group is 3-7, the deformation of each pass is 8%-20%, and the deformation of each fire is 30%-65%;

[0013] (4) After cold drawing to the target diameter, surface treatment is performed to obtain the finished wire.

[0014] Furthermore, the titanium alloy wire composition in step (1) comprises the following mass percentages: Al: 5.5-6.3%, V: 3.5-4.2%, Fe≤0.20%, O≤0.10%, C≤0.06%, H<0.01%, N≤0.03%, Si<0.05%, and the remainder is Ti.

[0015] Furthermore, in step (3), when the target diameter is between 1.0 and 3.0 mm, the diameter of the raw material wire for the drawing process is 1.5 to 4 mm; when the target diameter is between 0.2 and 1.0 mm, the diameter of the raw material wire for the drawing process is 0.5 to 1.5 mm; and when the target diameter is 1.0 mm, either drawing process A or B can be used.

[0016] Furthermore, the vacuum heat treatment temperature in step (2) and step (3) is 700-900°C, the holding time is 30-90 minutes, and the vacuum degree is 10 -3 ~10 -4 Pa; the surface lubrication treatment process is to attach an inorganic salt lubricant to the surface of the titanium alloy wire and dry it at 90 to 150°C.

[0017] Furthermore, the inorganic salt lubricant is obtained by mixing nano-montmorillonite K-10 and sodium polyvinyl alcohol sulfate in a mass ratio of 3:1. The attachment process is as follows: the inorganic salt lubricant is dissolved in a dissolution tank at 90-150°C, and after dissolution, the titanium alloy wire passes through or is immersed in the inorganic salt lubricant in the dissolution tank, and the titanium alloy wire is kept in the inorganic salt lubricant for 20-40s. The attachment amount of the inorganic salt lubricant on the titanium alloy wire is 5-10g / m 2 .

[0018] Furthermore, in the multi-group and multi-pass bright surface cold drawing process described in step (3), when the target diameter is 1.0-3.0 mm, the preferred number of groups is 3-5, the preferred number of passes in each group is 2-4, the preferred deformation per pass is 9%-16%, the deformation per single pass gradually decreases, the preferred deformation per fire is 30%-45%, and the drawing speed is 15-35 m / min; when the target diameter is 0.2-1.0 mm, the preferred number of groups is 3-5, the preferred number of passes is 4-6, the preferred deformation per pass in each group is 8%-16%, the deformation per single pass is the same, the preferred deformation per fire is 30%-55%, and the drawing speed is 15-35 m / min.

[0019] Furthermore, the surface treatment process described in step (4) is:

[0020] A. When the target diameter is between 1.0 and 3.0 mm, the wire is mechanically polished and cleaned;

[0021] or B, when the target diameter is 0.2 to 1.0 mm, the wire is electropolished and cleaned.

[0022] Furthermore, in the electrolytic polishing process, the electrolyte is 1L of solution prepared by adding 200ml of hydrofluoric acid (mass fraction 33%) and 500g of chromic anhydride (purity 99.9%) to water, and the current density is 0.4-1.0A / cm 2 , the voltage is set to 50-60V, and the polishing speed is 10-30m / min.

[0023] Furthermore, the cleaning process is to first clean in a weak alkaline cleaning solution with a pH of 8.0 to 9.0, and then clean in water using ultrasonic waves;

[0024] When the target diameter is 1.0 mm, either surface treatment process A or B can be used.

[0025] A titanium alloy wire prepared according to the preparation method of the present invention is characterized in that the wire diameter is 0.2-3 mm and the grain size grade is 10-15.

[0026] Furthermore, the grain size of the titanium alloy wire φ2.84 mm is level 10, the grain size of φ1.0 mm is level 12, the grain size of φ0.2 mm is level 15, and the organizational state is an equiaxed organization in the α+β two-phase region.

[0027] Advantages and beneficial effects of the present invention

[0028] 1. The cold drawing preparation process of the present invention can affect the microstructure and mechanical properties of titanium alloy wires by different deformation amounts of different passes and different fire times, and finally obtain titanium alloy wires with good microstructure and a yield rate of more than 80%. And the mechanical properties meet the requirements.

[0029] 2. The present invention can achieve a drawing rate of 15 to 35 m / min through a specific cold drawing preparation process combined with a heat treatment process, greatly improving production efficiency.

[0030] 3. The present invention is a bright surface drawing, which avoids the problem of low yield rate of frequent peeling of oxide scale drawing in the prior art. For φ0.5mm-φ0.2mm thin wires, the bright surface drawing reduces the problem of increased frequency of wire breakage caused by depressions on the wire surface caused by the treatment of oxide scale on the wire surface. At the same time, it solves the problem of increased oxygen content in oxide scale drawing, which has great practicality in production.

[0031] 4. The cold drawing preparation process of the present invention is carried out in the α+β two-phase region. The material undergoes high-temperature annealing and solid solution to obtain a large proportion of the β phase that is easy to deform and draw, and then undergoes cold drawing to crush and refine the grains to obtain fine equiaxed wire with high tensile strength. After multiple cold drawing passes with large deformation, the tensile strength of the obtained wire is ≥1350MPa, which is higher than the tensile strength of TC4ELI titanium alloy wire required in the standard GB / T3623-2007, which is ≥925MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The equilibrium phase transformation diagram of TC4 titanium alloy

[0033] Figure 2 Metallographic diagram of titanium alloy wire φ2.84mm

[0034] Figure 3 Metallographic diagram of titanium alloy wire φ1.0mm

[0035] Figure 4 Metallographic diagram of titanium alloy wire φ0.2mm

[0036] Figure 5 Different grain orientations of adjacent atoms in titanium alloy wire φ0.2 mm

[0037] Figure 6This is a photo of the bright surface of titanium alloy wire φ0.2mm after drawing DETAILED DESCRIPTION

[0038] The present invention is described in detail below with reference to the accompanying drawings and embodiments.

[0039] The cold drawing preparation process of the present invention is carried out in the α+β two-phase region. The material undergoes high-temperature annealing and solid solution to obtain a large proportion of the β phase that is easy to deform and draw, and then undergoes cold drawing to crush and refine the grains to obtain fine equiaxed wire. The present invention makes full use of the performance of the heat-affected zone of the titanium alloy during the heat treatment process during the cold drawing of the titanium alloy wire. After each bright surface cold drawing, the wire is heat treated and solid solution is performed. The heat treatment temperature is 700-900°C, the heat preservation time is 30-90 minutes, and the solid solution cooling method is liquid argon gas cooling to obtain a supersaturated solid solution and increase the percentage of the β phase, such as Figure 1 As shown, the plastic deformation capacity of the material is greatly improved.

[0040] The die used for cold drawing in the embodiment is a booster die: the booster die is a set of combined dies, which adds a pressure cavity in front of the drawing die to increase the adhesion of the lubricating powder and the wire, thereby greatly increasing the lubrication effect of wire drawing.

[0041] Example 1

[0042] This embodiment provides a method for preparing a high-strength titanium alloy wire with a diameter of 1.0 mm and a bright surface by cold drawing, and the specific steps are as follows:

[0043] (1) Preparing titanium alloy wire discs: The chemical composition of the titanium alloy wire discs processed by the bright surface cold drawing preparation process in this embodiment is as follows, by mass percentage: Al: 6.25%, V: 4.2%, Fe: 0.20%, O: 0.10%, C: 0.06%, N: 0.02%, H: 0.008%, Si: 0.03%, and the remainder is Ti; the diameter of the titanium alloy wire disc is 3.0 mm.

[0044] (2) Heat treatment: The titanium alloy wire coil is subjected to rounding and peeling treatment at 700°C to obtain a titanium alloy wire raw material with a diameter of 2.84 mm. The rounded and peeled titanium alloy wire raw material is placed in a vacuum annealing furnace with a vacuum degree of 10 - 3 Pa, heat to 700-900°C, specifically 850°C here, keep warm for 30-90min, specifically 1h here, take out of the furnace and quickly cool to room temperature in liquid argon.

[0045] (3) Surface lubrication treatment: The surface of the titanium alloy wire after vacuum annealing was roughened, and nano-montmorillonite (K-10) with a particle size distribution of 20 to 60 nm and sodium sulfate of fatty alcohol polyvinyl ether (commercially available from Hubei Kewode Chemical) were mixed in a mass ratio of 3:1, and dissolved in a dissolution tank of 3 m long and 0.3 m wide at 100°C. After dissolution, the titanium alloy wire was passed through the lubricant solution in the dissolution tank. The lubricant evenly adhered to the surface of the titanium alloy wire to form a lubricating film with an adhesion amount of 5 to 10 g / m 2 , here specifically 8g / m 2 , dried in a blast dryer at 100℃ to achieve interface lubrication effect.

[0046] (4) Cold drawing: The titanium alloy wire after surface lubrication is cold drawn to a bright surface. The drawing process is as follows: 4 groups of 4 drawing passes are used, and the deformation of each single drawing pass in each group gradually decreases. The deformation of the four passes are 13.2-13.6%, 12.3-12.6%, 11.2-11.8% and 9.8-10.9% respectively. The cumulative deformation of each group, that is, the deformation of the fire pass, does not exceed 42%. The drawing speed is 15m / min. After the 1-3 groups of drawing processes are completed, they need to be heat treated and surface lubricated before the next group of drawing can be carried out.

[0047] The specific process of heat treatment is as follows: put the titanium alloy wire after the previous drawing into a vacuum annealing furnace with a vacuum degree of 10 -3 Pa, raise the temperature to 850℃, keep it at that temperature for 1h, take it out of the furnace and quickly cool it to room temperature in liquid argon.

[0048] The surface lubrication process is the same as step (3).

[0049] After 4 sets of drawing, the wire is mechanically polished to remove surface impurities, and the surface oil is removed by passing through a weak alkaline cleaning solution (sodium bicarbonate solution with a mass fraction of 2%) with a pH of 8.3, and then cleaned in a pure water ultrasonic tank, and finally a φ1.0mm finished wire is obtained. The 4 sets of 4-pass drawing process are shown in Tables 1 to 4.

[0050] Table 1 The first group of drawing

[0051]

[0052] Table 2 The second group of drawing

[0053]

[0054]

[0055] Table 3 The third group of drawing

[0056]

[0057] Table 4 The fourth group of drawing

[0058]

[0059] Example 2

[0060] This embodiment provides a method for preparing a high-strength titanium alloy wire material φ0.2 mm by bright cold drawing, and the specific steps are as follows:

[0061] Take the φ1.0 mm titanium alloy wire prepared in the above-mentioned Example 1, and perform bright surface cold drawing after heat treatment and surface lubrication. The heat treatment and surface lubrication process are the same as the heat treatment and surface lubrication process of the cold drawing process in step (4) of Example 1, except that the heat treatment temperature is 830°C. Five groups of five drawing passes are adopted, and the deformation of each group in a single drawing pass is roughly the same, and the deformation of a single pass is 9.6-12.8%. The cumulative deformation of each group, i.e., the deformation of each fire, does not exceed 50%. The drawing speed is 20m / min. After the 1-4 groups of drawing processes are completed, they need to undergo heat treatment and surface lubrication before the next group of drawing is carried out. The heat treatment and surface lubrication process are the same as the heat treatment and surface lubrication process of the cold drawing process in step (4) of Example 1, and the only difference is that the heat treatment temperature is 830°C.

[0062] After 5 sets of drawing, the wire was first electropolished: the electrolyte was 1L solution prepared by adding 200ml hydrofluoric acid (mass fraction 33%) and 500g chromic anhydride (purity 99.9%) to water, and the current density was 0.8A / cm 2 , the voltage is set to 60V, the polishing speed is 20m / min; then the surface oil is removed by passing through a weak alkaline cleaning solution (sodium bicarbonate solution with a mass fraction of 2%) with a pH of 8.3, and then the wire is cleaned by a pure water ultrasonic tank, and finally a φ0.2mm finished wire is obtained. The 5 groups and 5 passes of the drawing process are shown in Tables 5 to 9.

[0063] Table 5 The first group of drawing

[0064]

[0065] Table 6 Second group drawing

[0066]

[0067]

[0068] Table 7 The third group of drawing

[0069]

[0070] Table 8 The fourth group of drawing

[0071]

[0072] Table 9 Fifth group drawing

[0073]

[0074] The titanium alloy wires with diameters of φ1.0 mm and φ0.2 mm prepared in the above embodiment were measured according to the requirements of the wire mechanical properties standard GB / T 228.1-2021, and the test results are shown in Table 10.

[0075] Table 10 Mechanical properties

[0076]

[0077] By comparing the tensile strength in standard GB / T3623, the wire material in the present invention has a higher tensile strength. Figure 2-Figure 4 It can be seen from the grain size shown in the metallographic diagram that the grain size of the titanium alloy disc round material φ2.84mm is 10th grade, the grain size of the titanium alloy wire material φ1.0mm in Example 1 is 12th grade, and the grain size of the titanium alloy wire material φ0.2mm in Example 2 is 15th grade. It is precisely because the grains of the titanium alloy wire material obtained by the process of the present invention are relatively small, and the adjacent atoms have different grain orientations, such as Figure 5 As shown in the figure, during plastic deformation, dislocation movement must pass through this common grain boundary, and fine grains have a larger grain boundary area to hinder dislocation movement; in addition, the orientations of the two grains are different, and the dislocation entering the grain must change its direction of movement. When the orientation difference is large, it is more difficult. Therefore, the titanium alloy wire prepared in the present invention has a high tensile strength. The finished product of titanium alloy wire φ0.2mm is shown in the figure. Figure 6 , with a glossy surface.

[0078] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-strength titanium alloy wire with a bright surface by cold drawing, characterized in that: The following steps are involved: (1) Taking titanium alloy wire raw material; (2) subjecting the titanium alloy wire to vacuum heat treatment and surface lubrication treatment; (3) performing multiple groups of multiple passes of bright surface cold drawing processes, and performing vacuum heat treatment and surface lubrication treatment between each group of cold drawing processes; The multi-group multi-pass bright surface cold drawing process, A. When the target diameter is 1.0-3.0mm, the number of groups is 3-6, the number of passes in each group is 2-6, the deformation of each pass is 8%-20%, and the deformation of each fire is 30%-50%; Or B, when the target diameter is 0.2-1.0mm, the number of groups is 3-6, the number of passes in each group is 3-7, the deformation of each pass is 8%-20%, and the deformation of each fire is 30%-65%; (4) After cold drawing to the target diameter, surface treatment is performed to obtain the finished wire.

2. The preparation method according to claim 1, characterized in that: The titanium alloy wire material of step (1) comprises the following mass percentages: Al: 5.5-6.3%, V: 3.5-4.2%, Fe≤0.20%, O≤0.10%, C≤0.06%, H<0.01%, N≤0.03%, Si<0.05%, and the remainder is Ti.

3. The preparation method according to claim 1, characterized in that: In step (3), when the target diameter is between 1.0 and 3.0 mm, the diameter of the raw material wire for the drawing process is 1.5 to 4.0 mm; when the target diameter is between 0.2 and 1.0 mm, the diameter of the raw material wire for the drawing process is 0.5 to 1.5 mm; and when the target diameter is 1.0 mm, either drawing process A or B can be used.

4. The preparation method according to claim 1, characterized in that: The vacuum heat treatment temperature in step (2) and step (3) is 700-900°C, the holding time is 30-90 minutes, and the vacuum degree is 10 -3 ~10 -4 Pa; the surface lubrication treatment process is to attach an inorganic salt lubricant to the surface of the titanium alloy wire and dry it at 90 to 150°C.

5. The preparation method according to claim 4, characterized in that: The inorganic salt lubricant is obtained by mixing nano-montmorillonite K-10 and sodium polyvinyl alcohol sulfate in a mass ratio of 3:

1. The attachment process is as follows: the inorganic salt lubricant is dissolved in a dissolution tank at 90-150°C, and after dissolution, the titanium alloy wire passes through or is immersed in the inorganic salt lubricant in the dissolution tank, and the titanium alloy wire is kept in the inorganic salt lubricant for 20-40 seconds. The attachment amount of the inorganic salt lubricant on the titanium alloy wire is 5-10 g / m 2 .

6. The preparation method according to claim 1 or 3, characterized in that: In the multi-group and multi-pass bright surface cold drawing process described in step (3), when the target diameter is 1.0-3.0 mm, the preferred number of groups is 3-5, the preferred number of passes in each group is 2-4, the preferred deformation per pass is 9%-16%, the deformation per single pass gradually decreases, the preferred deformation per fire is 30%-45%, and the drawing speed is 15-35 m / min; when the target diameter is 0.2-1.0 mm, the preferred number of groups is 3-5, the preferred number of passes in each group is 4-6, the preferred deformation per pass is 8%-16%, the deformation per single pass is the same, the preferred deformation per fire is 30%-55%, and the drawing speed is 15-35 m / min.

7. The preparation method according to claim 1, characterized in that: The surface treatment process described in step (4) is: A. When the target diameter is between 1.0 and 3.0 mm, the wire is mechanically polished and cleaned; or B, when the target diameter is 0.2 to 1.0 mm, the wire is electropolished and cleaned.

8. The preparation method according to claim 7, characterized in that: The cleaning process is to first clean in a weak alkaline cleaning solution with a pH of 8.0 to 9.0, and then clean in water by ultrasonic cleaning; When the target diameter is 1.0 mm, either surface treatment process A or B can be used.

9. A titanium alloy wire prepared according to the preparation method of claim 1, characterized in that: The wire diameter is 0.2-3 mm, and the grain size grade is 10-15.

10. The titanium alloy wire prepared by the preparation method according to claim 9, characterized in that: The grain size of titanium alloy wire φ2.84mm is level 10, the grain size of φ1.0mm is level 12, the grain size of φ0.2mm is level 15, and the organizational state is equiaxed organization in the α+β two-phase region.

Citation Information

Patent Citations

  • Efficient wiredrawing fluid capable of realizing surface metal rust prevention

    CN103966004A

  • Cold drawing preparation method for TB9 titanium alloy disc round wire with lubricating coating

    CN113210448A

  • Treatment method of heat-resistant alloy cold heading steel wire

    CN113462869A

  • Copper wire drawing process based on modified wire drawing liquid treatment

    CN116727475A

  • High-resistance metal alloy wire drawing lubricating liquid and preparation method thereof

    CN117165356A